METODE PENDIDIKAN ANAK DALAM KELUARGA MENURUT ABDULLAH NASHIH ULWAN DAN RELEVANSINYA DENGAN PENDIDIKAN ANAK DALAM KELUARGA DI KELURAHAN MAJAPAHIT KOTA LUBUKLINGGAU - Adi Sutrisno (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2017)
This study aims to describe  the  method of education of children in the  fami-ly according to the  concept of ‘ Abd Tarbiyatul  Nashih  Ulwan in Awlad fil Islam and  describe  the  relevance of the  method of education of children in the  family according to the  concept of ‘ Abd Tarbiyatul  Nashih  Ulwan in Awlad fil Islam with education in Neighborhoods of Majapahit city of Lubuklinggau. This study uses descriptive  qualitative  approach. In obtaining the  data,  the  authors use tech-niques of observation, interviews, a list of the checklist,  and  documentation. From the results of this research were obtained results that: child  education Methods  in the  family according to the  concept of ‘ Abd Tarbiyatul  Nashih  Ulwan in Awlad fil Islam, namely, first, the  educational method with the  example. Se-cond,  education with indigenous customs.  Third,  education with advice. Fourthly,  the education by providing oversight.  Fifth, education by giving away penalties. The fifth method of education are the most important methods for achieving  the goal of education is the morals  of the child. Child education methods with example parents according to Abdullah  Nashih  Ulwan still relevant  applied in Kelurahan Majapahit  City Lubuklinggau, among  them  the example of parents in adopting good example, in generosity, ex-ample parents in avoiding bad morals. Child education methods with customs ac-cording  to Abdullah  Nashih  Ulwan still relevant  applied in district  Majapahit  city of Lubuklinggau. Method of education with advices according to Abdullah  Nashih  Ulwan still relevant  applied in Kelurahan Majapahit  city of Lubuklinggau. Method of educa-tion of a child with attention according to Abdullah  Nashih  Ulwan still relevant  applied in district  Majapahit City Lubuklinggau, as parents pay attention to or su-pervise the conditions of the faith of children, pay attention to the moral and be-havior of the child, and  pay attention to the implementation of the children’s wor-ship. Methods  of education by providing punishment according to Abdullah  Nashih  Ulwan still relevant  applied in district  Majapahit  City Lubuklinggau, if teaching, advice and  oversight  are not followed by the son, then  the final path  is giving the punishment on a child that  aim to educate